An Evolutionary Multilayer Perceptron-Based Large-Signal Model of GaN HEMTs Including Self-Heating and Trapping Effects - Wenrui Hu (Institute of Electrical and Electronics Engineers (IEEE), 2021)
10.1109/TMTT.2021.3132892